ANTIOXIDANT AND ANTIHEMOLYTIC ACTIVITY OF AN ENDANGERED PLANT SPECIES, HILDEGARDIA POPULIFOLIA (ROXB.) SCHOTT & ENDL. - M., Saradha; Paulsamy, S.; Vinitha, R. (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: The present study was aimed at to estimate total content of ascorbic acid, saponins and condensed tannins and to evaluate the antioxidant activity and antihemolytic activity of methanolic extracts of leaf and stem bark parts of Hildegardia populifolia. Methods: Antioxidant activity was carried out by studying nitric oxide scavenging activity, inhibition of Î² â€“ carotene bleaching activity and antihemolytic activity also studied. Results: Higher amount of ascorbic acid (93.47 g AA/100 g extract), saponins (18.81 g DE/100g extract) and condensed tannins (0.70 mg LE/g dry sample) was observed in methanolic leaf extract than that of the stem bark extract. Nitric oxide scavenging and Î² â€“ carotene bleaching activity were relatively higher in stem bark extract (IC50 -122.60 and 56.67percent respectively). Leaf extract has higher percentage of antihemolytic activity than that of the stem bark extract. Â Conclusion: The results of the study confirmed that the studied plant might indeed be potential sources of natural antioxidant and antihemolytic agents. Key words: Antioxidant, antihemolytic activity, Hildegardia populifolia.